Effect of physical processing methods on the content of biologically active substances in flowers of dandelion (Traxacum officinale Wigg.) - Косоголова, Л. О.; Лошицький, П. П.; Чабанюк, Л. Л.; Яблонська, К. М. (Problems of Environmental Biotechnology, 2017)
In the article, the influence of electromagnetic radiation of different frequencies, as well as the temperature on the extraction of quercetin from dandelion flowers (Taraxacum oficinale Wigg) is considered. The extraction regimes are established, in which an increase in the amount of quercetin in the extract occurs. The results of the investigations indicate that at an excessively high frequency (57–68 GHz), a maximal increase in the amount of quercetin in the extract is observed during a 15-minute irradiation with an electromagnetic field. In ultrasonic treatment (800–860 kHz), a maximal increase in quercetin in the extract was observed with a 20-minute irradiation (power of 5 W) and with 15-minute irradiation (power 7 W). During thermal processing, the maximum increase in quercetin in the extract was observed at 60 °C for 30 minutes, 55 °C for 1 hour, and at 60 °C for 1.5 hours of treatment.